The experience of İstanbul Protocol: efficiency, quality, difficulties in practice - Turan Yurtsever, Nurşen (The European Research Journal, 2019)
Objectives: Physicians who witness torture and ill treatment can be placed in a difficult position if their evidence was not accurately documented. The guidelines and ethical codes of the Istanbul Protocol require doctors to attend first and foremost to the well-being of their patients and to remain bound by the principles of medical ethics. The objective of this study was to compare the efficiency and the quality of the examination of detainees or alleged torture cases by medical doctors and the difficulties encountered in this activity.Methods: A questionnaire was developed and sent to physicians in Black Sea Shore region of Turkey before and 1 year after their receiving training according to the Istanbul Protocol.Results: There were 42 physicians who had undergone training according to the Istanbul Protocol and had answered the questionnaire; 28.6% of these were women and 71.4% men. These physicians applied the Istanbul Protocol more frequently after having received training on the Protocol Manual as compared to before the training. The 52.4% of these physicians reported having been the object of violence or intimidation. Conclusions: It was determined that the physicians' knowledge of physical and psychological examination increased following their training according to the Istanbul Protocol.